# What is the value of x in the equation?

How to solve equation: (x-2)/3+1/6=5/6

﻿
1. Solutions: x=4

Detailed explanation:

Look at 5/6

Moved these terms to the left: – 5/6

It becomes: (x – 2)/3 + 1/6 – 5/6=0

Look at 1/6-5/6

Added fractions or integers together, it becomes: (x – 2)/3 – 4/6=0

Look at 4/6

Factors 4 and 6 have greatest common factor of 2. Reducing fraction.

It becomes: (x – 2)/3 – 2/3=0

Look at (x-2)/3

Expanded term 1/3 by using associative property on (x – 2)

It becomes: x/3 – 2/3 – 2/3 = 0

Look at – 2/3 – 2/3

It becomes: x/3 – 4/3 = 0

Move the 4/3 term to the right of the = sign, so that term involving the variable are on the left and the right side of the equation has only numbers.

It becomes: x/3 = 4/3

3x = 12

x = 12/3

x = 4

Psst... Stuck with your assignment? 😱  Erica
Online Psst... Stuck with your assignment? 😱
Do you need an essay to be done?
Yes
Other assignment What type of assignment 📝 do you need?
• Article review
• Case study
• Coursework
• Report
• Research Paper
• Other Assignment How many pages (words) do you need? Let's see if we can help you!